A new two-lane lattice hydrodynamic model on a curved road accounting for the empirical lane-changing rate. Issue 4 (28th August 2020) - Wang, Qingying; Cheng, Rongjun; Ge, Hongxia
Abstract : Purpose: The purpose of this paper is to explore how curved road and lane-changing rates affect the stability of traffic flow. Design/methodology/approach: An extended two-lane lattice hydrodynamic model on a curved road accounting for the empirical lane-changing rate is presented. The linear analysis of the new model is discussed, the stability condition and the neutral stability condition are obtained. Also, the mKdV equation and its solution are proposed through nonlinear analysis, which discusses the stability of the extended model in the unstable region. Furthermore, the results of theoretical analysis are verified by numerical simulation. Findings: The empirical lane-changing rate on a curved road is an important factor, which can alleviate traffic congestion. Research limitations/implications: This paper does not take into account the factors such as slope, the drivers' characters and so on in the actual traffic, which will have more or less influence on the stability of traffic flow, so there is still a certain gap with the real traffic environment. Originality/value: The curved road and empirical lane-changing rate are researched simultaneously in a two-lane lattice hydrodynamic models in this paper. The improved model can better reflect the actual traffic, which can also provide a theoretical reference for the actual traffic governance.